2013
DOI: 10.1093/hmg/ddt430
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics meets metabolomics: an epigenome-wide association study with blood serum metabolic traits

Abstract: Previously, we reported strong influences of genetic variants on metabolic phenotypes, some of them with clinical relevance. Here, we hypothesize that DNA methylation may have an important and potentially independent effect on human metabolism. To test this hypothesis, we conducted what is to the best of our knowledge the first epigenome-wide association study (EWAS) between DNA methylation and metabolic traits (metabotypes) in human blood. We assess 649 blood metabolic traits from 1814 participants of the Koo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
140
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 171 publications
(154 citation statements)
references
References 32 publications
9
140
1
2
Order By: Relevance
“…This finding was further validated in WB by pyrosequencing and ampliconseq. Interestingly, association of TXNIP hypo-me at the same CpG3 with type 2 diabetes and related traits (including fasting glucose, HbA1C, and insulin resistance) (57-60), serum metabolites related to diabetes (61), and high blood triglycerides (62) in WB DNA from various cohorts was recently reported. Because Txnip was associated with lipids in a mouse model (63), we reanalyzed methylation differences in cases vs. controls at CpG3 after adding triglycerides at the EDIC Study baseline as a covariate.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was further validated in WB by pyrosequencing and ampliconseq. Interestingly, association of TXNIP hypo-me at the same CpG3 with type 2 diabetes and related traits (including fasting glucose, HbA1C, and insulin resistance) (57-60), serum metabolites related to diabetes (61), and high blood triglycerides (62) in WB DNA from various cohorts was recently reported. Because Txnip was associated with lipids in a mouse model (63), we reanalyzed methylation differences in cases vs. controls at CpG3 after adding triglycerides at the EDIC Study baseline as a covariate.…”
Section: Discussionmentioning
confidence: 99%
“…A recent epigenome-wide association study (EWAS) of DNA methylation with metabolomics has shown that DNA methylation also plays an important role in human metabolism (Petersen et al 2014). In this study, we briefly highlight one diabetes-relevant example from that study: the thioredoxin-interacting protein (TXNIP) plays a functional role in glucose regulation.…”
Section: The Role Of Genetic Variance and The Intermediate Metabolic mentioning
confidence: 99%
“…Following the central dogma of molecular biology, genomics, transcriptomics and proteomics are correlated ‘by definition’. Furthermore, metabolite concentrations are influenced by genetic variants (Shin et al ., 2014) and epigenetic factors (Petersen et al ., 2014) mediated through changes in gene expression or enzyme activity. Methylation levels do not only influence the gene expression (Jaenisch & Bird, 2003), but are also correlated with gene variants (Bell et al ., 2012) and environmental factors (Breitling et al ., 2011).…”
Section: From Omics To Systems Biologymentioning
confidence: 99%